Surgical treatment of posttraumatic spinal cord tethering and syringomyelia: a retrospective cohort investigation of cost, reimbursement, and financial sustainability - Phillip Jaszczuk; Denis Bratelj; Crescenzo Capone; Susanne Stalder; Marcel Rudnick; Rajeev K. Verma; Tobias Pötzel; Michael Fiechter (BMC Surgery)
Abstract Background Posttraumatic spinal cord tethering and syringomyelia are considered disabling diseases in patients with spinal cord injury. In symptomatic patients, surgical management can achieve promising clinical outcomes. As the raising economic pressure might jeopardize optimal and thus personalized patient care, we aimed to exemplify expenses of surgical treatment in contrast to reimbursement by the Swiss diagnosis related group (DRG) system. Methods This retrospective investigation includes 60 patients who underwent surgery for spinal cord tethering and syringomyelia. The duration of surgeries was used to estimate the costs of care in the operating room (OR) considering established bench marks. Coverage of costs was calculated by comparing Swiss DRG reimbursements with the expenses from the investigated cases. Results The mean duration of surgeries was 251.0 ± 93.5 min while 2.8 ± 1.4 vertebral segments were treated by spinal cord untethering. The mean OR costs (in USD) were $9,401.2±$3,500.2 (range $4,119.5 to $20,223.0). The mean reimbursement and the ratio of OR costs to reimbursement (in USD) were $24,122.5±$7,409.3 (range $17,249.8 to $31,977.1) and 0.41 ± 0.15 (range 0.14 to 0.74) for standard, and $39,106.0±$4,028.6 (range $35,369.1 to $43,376.8) and 0.24 ± 0.08 (range 0.10 to 0.47) for complex cases, respectively. The estimated costs of surgeries were different from reimbursements (p = 0.005). Conclusions Although the cost of surgical management of patients with posttraumatic spinal cord tethering and syringomyelia are principally covered, it remains questionable if total hospital expenses are sufficiently outweighed by the current reimbursement system. This could potentially limit the availability of best medical care and might endanger personalized patient management.